Assessment of Documented Vaccination of Adolescent Schoolchildren in Various Cities of Russian Federation - Leyla S. Namazova-Baranova; Marina V. Fedoseenko; Firuza Ch. Shakhtatinskaya; Kamilla E. Efendieva; Elena V. Kaytukova; Elena A. Vishneva; Tatiana A. Kaliuzhnaia; Svetlana V. Tolstova; Margarita A. Soloshenko; Arevaluis M. Selvyan; Elizaveta V. Leonova; Snezhana D. Timoshkova (Педиатрическая фармакология)
Epidemiological surveillance of preventive vaccinations implementation is the most crucial component in the immunoprophylaxis organization. Assessment of documented vaccination coverage indicators allows to determine the quality of routine preventive vaccination and indirectly evaluate the possible state of population immunity to vaccine preventable diseases. Continuous quality control of routine vaccination, therefore, is a component of the system for epidemic management of infectious diseases. Specific decisions should be based on its results to improve preventive vaccination quality.Сomparative analysis of the vaccination history in adolescents (studying in schools in large cities of different federal districts of Russian Federation) and recommended national immunisation schedule allowed to identify widespread systemic mistakes of vaccination status. These issues led to the uprise and spread of vaccine preventable diseases. The study results confirmed the topicality of awareness-raising activities among medical staff working on preventive vaccination. Moreover, long-standing need of vaccination schemes correction is also important through development of medical technology aimed on improvement of catch-up vaccination approach.